Metode Mengajar Guru Sekolah Minggu Dengan Menggunakan Teknologi Informasi Dan Komunikasi - Ayu Lestari; Riste Tioma Silaen; Mozes Lawalata (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The teaching method is a method used by a Sunday school teacher in teaching, guiding, advising and directing Sunday school children in understanding the word or works of God by using ICT. However, in reality, Sunday school teachers do not make use of ICT in organizing teaching and learning activities, even though they already understand that ICT greatly supports or helps the child's level of mastery of subject matter as a tool for achieving teaching and learning goals. In this study, the steps taken by the author to examine the literature search method. Literature search includes searching from various sources of literature from magazines, books and other sources to facilitate research, the method is to find material related to the discussion of this article, both physically and digitally or manually. Thus, so that learning can be effective and not boring, Sunday school teachers are required to be able to use ICT as a learning method when teaching. So in this case the Sunday school teacher will find it easier to provide learning as well as children will find it easier to capture and understand learning, not get bored in learning, and will have an interest and curiosity in the lessons being studied. The use of ICT as a teaching method for Sunday school teachers will generate new desires and interests for children and the media can control the pace of learning and provide a comprehensive experience for children from concrete and abstract things. So, teaching methods using information and communication technology will have a major influence or impact on learning outcomes with the desired goals.